1995
DOI: 10.1128/aac.39.12.2718
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity and cross-resistance evaluations of a series of human immunodeficiency virus type-1-specific compounds related to oxathiin carboxanilide

Abstract: A series of compounds related to the nonnucleoside reverse transcriptase (RT) inhibitor (NNRTI) oxathiin carboxanilide (UC84) were evaluated for activity against the human immunodeficiency virus (HIV) to determine structural requirements for anti-HIV activity. Twenty-seven compounds representative of the more than 400 Uniroyal Chemical Company (UC) compounds were evaluated for structure-activity relationships. Several of the compounds evaluated were highly active, with 50% effective concentrations in the nanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
81
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 46 publications
0
81
0
Order By: Relevance
“…All experiments for antiviral activity were performed with triplicate samples in RPMI 1640 medium supplemented with 15% fetal bovine serum, L-glutamate (2 mM), penicillin (100 U/ml), and streptomycin (100 g/ml). HIV-1 replication in PBMC and monocyte/macrophage cultures was determined by measurement of the RT activity in the supernatant and p24 antigen expression, respectively, by enzymelinked immunosorbent assay (Coulter, Hialeah, Fla.) (2,3). Cell viability was determined by measurement of formazan dye reduction in replicate cultures in CellTiter reagent (Promega, Madison, Wis.).…”
Section: Methodsmentioning
confidence: 99%
“…All experiments for antiviral activity were performed with triplicate samples in RPMI 1640 medium supplemented with 15% fetal bovine serum, L-glutamate (2 mM), penicillin (100 U/ml), and streptomycin (100 g/ml). HIV-1 replication in PBMC and monocyte/macrophage cultures was determined by measurement of the RT activity in the supernatant and p24 antigen expression, respectively, by enzymelinked immunosorbent assay (Coulter, Hialeah, Fla.) (2,3). Cell viability was determined by measurement of formazan dye reduction in replicate cultures in CellTiter reagent (Promega, Madison, Wis.).…”
Section: Methodsmentioning
confidence: 99%
“…Because both groups of inhibitors bind to different sites on RT in a nonexclusive manner (12), combinations of nucleoside analogs and non-nucleoside inhibitors might have a potential synergistic inhibitory effect on HIV-1 RT. Synergistic inhibition of HIV replication in cell culture has been reported for many combinations of nucleoside and non-nucleoside RT inhibitors (13)(14)(15)(16). Nevertheless, several other studies have shown that the same combinations showed no synergy in inhibiting RT activity in vitro (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Antiviral bioassays. CV-N and its functional homologs were evaluated against a range of virus isolates by standardized cytopathic effect (CPE) inhibition assays (9) or specific antiviral assays as specified in Tables 1 and 2. In all assays the cytotoxic effects of compounds were measured spectrometrically by formazan dye reduction using either XXT {2,3-bis(2-methoxy-4-nitro-5-sulfophenyl)-5-[(phenylamino)carbonyl]-2H-tetrazolium hydroxide} or MTS [3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium salt] (CellTiter 96; Promega, Madison, Wis.).…”
Section: Methodsmentioning
confidence: 99%